Percy Jackson and the battle of the labyrinth - Riordan, Rick (Puffin New York, 2009)
Percy Jackson and the Battle of the Labyrinth follows Percy and his friends as they navigate the treacherous Labyrinth to prevent the rise of the Titan lord Kronos, facing mythical creatures and ancient magic in a thrilling quest.